If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 3) = 11x + 6 Reorder the terms: 4(3 + 2x) = 11x + 6 (3 * 4 + 2x * 4) = 11x + 6 (12 + 8x) = 11x + 6 Reorder the terms: 12 + 8x = 6 + 11x Solving 12 + 8x = 6 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 12 + 8x + -11x = 6 + 11x + -11x Combine like terms: 8x + -11x = -3x 12 + -3x = 6 + 11x + -11x Combine like terms: 11x + -11x = 0 12 + -3x = 6 + 0 12 + -3x = 6 Add '-12' to each side of the equation. 12 + -12 + -3x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 6 + -12 -3x = 6 + -12 Combine like terms: 6 + -12 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 20=5y+5 | | 180=2x-18 | | 525.00+0.21x=600 | | 2t+7=t+9 | | 76-x=3x | | 7n+2=5n+20 | | 9x+4=8x+7 | | 4t^2+48t=160 | | -2v^2-1v+12=-3v^2+6v | | 2x+4y+.25z=100 | | (-8/5)x-6=-54 | | 4m+4=4(m+1) | | 6x-4+4x-6=180 | | 2x+46+x-18+x=180 | | y^2+2xy-3x^2=0 | | 525.00+0.21x=850.00+0.31x | | 2x+46+x-18=180 | | 525.00+0.21x=850.00+0.31 | | 6x-4+7x-4+5x+8=180 | | 12+6q(5-q)= | | -(1+6k)+4k=-8k-7(k+2) | | 117=8x+57 | | x+-5.5-4(5)=-18 | | 6x^3+11x^2-92x+15=3 | | 4y+5=-17 | | 6x^3+11x^2-92x+15=0 | | 3x-4=42 | | x^2-22x+121=144 | | 751-12=x | | -4(2-3p)=40+4p | | 238+419=x | | x-3=6x-7 |